Elevated Expression of Nrf-2 and ABCG2 Involved in Multi-drug Resistance of Lung Cancer SP Cells - Yang, B.; Ma, Y.-F.; Liu, Y. (Drug Research, 2015)
Background: Over expression of ATP-binding cassette (ABC) transporter protein (ABCG2) in side population cells plays a crucial role in the chemotherapeutic drug efflux. Constitutive expression of redox sensing transcritption factor Nrf2 was shown to be involved in regulation of ABCG2 expression and chemoresistance. In the current study we made an attempt to characterize the lung adenocarcinoma SP cells.Materials and Methods: We used FACs based Hoechst 33342 dye exclusion assay for purification of lung cancer SP cells. The sorted SP cells were subjected to drug resistance, sphere formation assays and gene expression analysis (Nrf2 and ABCG2).Results: We have identified 2.9% of SP cells from lung cancer whose prevalence is significantly reduced to 0.3% upon treatment with verapamil. RT-PCR and western blot analysis revealed that Nrf2 and ABCG2 were highly expressed in lung cancer SP cells. Further, these SP cells are resistant to several chemotherapeutic drugs, self-renewal, and highly tumorigenic than non-SP cells.Conclusions: Our data suggest that Nrf2-mediated ABCG2 over expression in lung adenocarcinoma SP cells might responsible for chemotherapy failure. Therefore, designing novel anticancer drugs that attenuates the Nrf2 and ABCG2 expression, makes SP cells more sensitive to chemotherapy and thus prevent the tumor relapse.
Keywords: cancer stem-like cells; side-population cells; self-renewal; Nrf2; chemoresistance